Study on the initiation mechanism and motion characteristics of the Daguangbao landslide and the slope stability evaluation method - Yu, Dejie; Liu, Lei; Ding, Yue; Yang, Fan; Zhang, Xiangyu (Frontiers in Built Environment, 2026)
Landslide triggered by earthquake has always been the hotspot due to its large scale, unique genesis, and complex kinematic processes. In this paper, the Daguangbao landslide in the 2008 Wenchuan Ms8.0 earthquake is selected as the research object. The initiation mechanism and motion characteristics of the Daguangbao landslide under seismic action are investigated, and the comprehensive evaluation method of slope stability is established. Firstly, a numerical model of the Daguangbao landslide is established according to the geological data before and after the earthquake. Secondly, the rock mass motion characteristics of Daguangbao landslide process are analyzed by FLAC3D, and the formation mechanism of landslide is explored by monitoring the displacement and velocity information of the slope during earthquake. Finally, a slope stability evaluation method is established based on the comprehensive weight and extension method. The stability evaluation of Daguangbao and other 10 slopes is carried out to verify the accuracy of the evaluation method. The specific conclusions are as follows: (i) Under the earthquake impact, displacement starts at the slope foot due to stress concentration, gradually spreading upward and peaking in the middle, causing vibration and fragmentation. (ii) The main sliding surface forms as friction resistance decreases between broken and downstream rock mass. The tension-shear action induced by the earthquake detaches the sliding body, causing high speed slides that accumulate under mountain barriers to form debris flow areas. (iii) The proposed evaluation method of slope stability has high accuracy and good prospects for engineering application.